Parasitological efficacy of antimalarials in the treatment and prevention of falciparum malaria in pregnancy 1998 to 2009: a systematic review. - Mcgready, R; White, N; Nosten, F (2011)
BACKGROUND: Pregnant women are at increased risk from malaria. Resistance to all classes of antimalarials has affected the treatment and prevention of malaria in pregnancy. OBJECTIVES: To review the therapeutic efficacy of antimalarials used for treatment and intermittent preventive treatment (IPT) in pregnancy. SEARCH STRATEGY: We searched MEDLINE and the Cochrane Library between January 1998 and December 2009 for publications using the medical subject headings: efficacy, antimalarials, malaria, pregnancy, pharmacokinetics, treatment, IPT and placenta positive. In May 2010 we searched the register of clinical trials (http://clinicaltrials.gov/) and of WHO (http://apps.who.int/trialsearch/) using 'malaria', and 'pregnancy' and 'treatment'. SELECTION CRITERIA: We identified 233 abstracts, reviewed 83 full text articles and included 60 studies. DATA COLLECTION AND ANALYSIS: Two authors entered extracted data to an excel spreadsheet. MAIN RESULTS: Parasitological failure rates, placenta positivity rates (assessed by microscopy) or both were reported in 44% (21/48), 46% (22/48) and 10% (5/48) of articles, respectively. Most pharmacokinetic studies (9/12) suggested dose optimisation. In 23 treatment studies 17 different antimalarial drugs were delivered in 53 study arms; 43.4% (23/53) reported a failure rate of < 5%; 83.3% of sulphadoxine-pyrimethamine (SP) arms and 9% of artemisinin combination therapy (ACT) arms had failure rates ≥ 10%. Placenta-positive rates (mostly reported in the context of IPT in pregnancy) were > 10% in 68% (23/34) of SP trial arms and > 15% in all seven chloroquine arms. The ACT provided lower parasitological failure and gametocyte carriage rates. AUTHOR'S CONCLUSIONS: Drugs used in pregnancy should aim for 95% efficacy but many currently deployed regimens are associated with much lower cure rates.